Computer Based Testing in Senior High School on National Examination - Alek Alek; Abdul Gafur Marzuki; Muhammad Farkhan; Dede Surahman; Dedi Daryanto; Sanidaya Febrianto (Indonesian Journal of Learning Education and Counseling, 2020)
The aim of this study is to investigate the students’ perception of computer-based testing in national examination and determine the extent to which cheating in exams would be eliminated by the adoption of CBT in National examination. Relevant to the purpose of the study, the researchers decide to use a qualitative case study since it was taken place in a natural setting and the data was collecting using questionnaire. This study conducted in one of senior high school in Jakarta Timur. Then, the participants in this study were 30 students of twelfth-grade students. The results of this study are almost 30 students give their perception that the CBT is the effective one for the students in the final examination and the CBT produces a good final examination the elimination of cheating cases in the national examination consumes time in each question.